2016
DOI: 10.1039/c6cp02130a
|View full text |Cite
|
Sign up to set email alerts
|

The conformational space of the neurotransmitter serotonin: how the rotation of a hydroxyl group changes all

Abstract: The 5-hydroxytryptamine receptors (5HTn) are optimized for 5-hydrotryptamine molecules, resulting in a significantly enhanced psychoactive response compared with the 4-, 6-, 7-isomers. This is despite their relatively similar energetic stabilities, excited state lifetimes and emission characteristics. In this work we investigate the conformational space of serotonin (5-hydroxytryptamine) using a combination of rotationally resolved electronic spectroscopy and ab initio calculations. The geometries of the four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Some experimental and theoretical attempts have been made to clarify 5-HT conformations [12,20–25]. Of these studies, LeGreve’s work [23] has reached the results close to ours.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Some experimental and theoretical attempts have been made to clarify 5-HT conformations [12,20–25]. Of these studies, LeGreve’s work [23] has reached the results close to ours.…”
Section: Discussionsupporting
confidence: 64%
“…The validity of this selection was confirmed on the basis of previous work by Wilke et al [12], in which our selected conformation was called anti -serotonin, and the other conformation was called syn -serotonin. They concluded that the anti -conformers are always more stable in the ground state [12]. In the present study, we prepared 12 molecular structures as the initial condition in gas phase.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…), which could preserve the catalyst from deactivation. The results confirmed that the catalyst was highly influenced by the temperature inside the reactor . Besides, the best design parameters of the tubular methanol synthesis reactor were obtained from a sensitivity analysis of operating parameters conducted above in this study.…”
Section: Resultsmentioning
confidence: 99%
“…However, inductive (+I or −I) effects and even through‐space effects also influence the electron distribution between the ligand and the chromophore. For the hydroxy and methoxy substituents, it has been found that the adjacent C‐atom to which the lone pairs of the O‐atom points, has the lower electron density . Thus, it is interesting to investigate the dipole moments of different rotamers of disubstituted benzenes, which either can talk to each other electronically ( ortho and para ), or communicate only via inductive effects ( meta ).…”
Section: Introductionmentioning
confidence: 99%